The Migration of the Arab Literary Minority in Europe: 'Alī Badr's Novels and His Vertical Mobilization - Luhuringbudi, Teguh; Wahhab, Muhbib Abdul; Asnawi, Tb. Ade (Universitas Islam Negeri Sunan Kalijaga, 2024)
This research is rooted in a profound appreciation for the rich literary heritage of Arab society from the past, which we seek to revive in the present. The primary objective of this study is to delve into the values, messages, and ideologies conveyed by the novelist 'Alī Badr through his novels: 'Bābā Sārtir' (2001), 'Shitā'u al-'Āilah' (2002), and 'al-Walīmah al-'Āriyah' (2004), as these literary works engage in global discourse. This study applies two approaches: the international relations perspective as the foundation for fostering global interconnectedness and the media perspective, which evaluates the extent to which Arabic novels influence and shape the universal discourse of humanity. The analysis within the international relations framework, utilizing Michael Barnett's constructivist perspective, seeks to uncover the dynamics of social interactions and the nuanced dimensions of power. This examination aims to understand the implications of Arab novelists' engagement with their European counterparts. The analysis within the media approach, using Gill Branston and Roy Stafford's globalization perspective, aims to capture global media narratives that encapsulate their evaluation of the presence and impact of 'Ali Badr's novels. This research concludes that the involvement of 'Alī Badr and his works in the European literary landscape not only serves as a platform for the contestation of global ideas depicted in his novels but also garners widespread global acclaim, as evidenced by numerous awards.